An overview of Elephant Conservation in India - Bisht, S. S. (Indian Forester, 2002)
Efforts for the conservation of the Elephant (Elephas maximus) in India were initiated in 1873 with the promulgation of the Madras Wild Elephant Preservation Act, 1873. But the earlier laws were quite liberal as regards capturing of elephants and permitted their killing under the pretext of protecting crop and public property. No attempt was made to control the ivory trade and protect habitat of elephants. As a result, elephant population in the country continued to decline. The elephant was included in Schedule I of the Wildlife (Protection) Act, 1972 on 5.10.1977. A number oflegislative measures were taken in the subsequent years which resulted in controlling the process of deforestation of elephant habitat and prohibiting ivory trade. Attempts for the conservation of elephants got a big boost in February 1992 when Government of India launched Project Elephant. As a result of various conservation measures, elephants now enjoy a comprehensive legal support and their population has gone up from 15,627 in 1980 to 28,274 in 2001. There has also been some reduction in the cases of human deaths caused by elephants. But the overall status of elephants and their habitat continues to be precarious. Incidences of killing of elephants by poachers for ivory and by farmers in retaliation to crop damage, are on the increase. Habitats and corridors of elephants are under tremendous pressure in many States on account of deforestation, encroachment and other biotic factors. In some regions, poaching of tuskers has disturbed the sex-ratio in elephant populations to alarming proportions. Human-elephant conflict has become a serious issue and the people are turning hostile to elephants and the forest staff. Status of domesticated elephants in India is also not satisfactory. The veterinary support for elephants is not adequate. It is necessary to make systematic and sustained efforts to deal with various problems concerning conservation of elephants. Tbe conservation strategies should also strive to nature and encourage the love and sympathy that a large number of people in India still have for elephants.